Enhancing Public Service Delivery in The Indonesian National Police: A Case Study of Driving License and Police Clearance Certificate Services at Waropen Police Station - Ripka Hawar, Angela; Sri Kartini, Dede; Alamsah Deliarnoor, Nandang; Indrawati Sagita, Novie (International Proceedings of Nusantara Raya, 2024)
According to the 2023 report of the Indonesian Ombudsman, the National Police (Polri) is an institution frequently reported for public service complaints, especially in regional areas. This issue is notably observed in providing SIM (Driver's License) and SKCK (Police Clearance Certificate) services by Waropen District Police in Papua Province. Improving public services in regional areas is crucial for the Polri to enhance public trust. Therefore, this study will analyze the optimization of SIM and SKCK services by the Waropen District Police, considering that Waropen Regency is a remote area and poses unique challenges for the Polri in providing public services. This research used Haywood's model of public service quality with three main elements: Professional Judgment, Physical Facilities, Processes and Procedures, and People's Behavior and Conviviality. A qualitative method through interview techniques was used in this research. The findings of this study indicate that efforts to improve SIM and SKCK services need to consider the professionalism of personnel, service facilities, and procedures, as well as the attitudes and behaviors of personnel.